A mobile platform for controlling and interacting with a do-it-yourself smart eyewear. Issue 1 (3rd April 2017) - Brun, Damien; Ferreira, Susan M.; Gouin-Vallerand, Charles; George, Sébastien
Abstract : Purpose: Smart eyewear, such as augmented or virtual reality headset, allows the projection of virtual content through a display worn on the user's head. This paper aims to present a mobile platform, named "CARTON", which transforms a smartphone into smart eyewear, following a do-it-yourself (DIY) approach. This platform is composed of three main components: a blueprint to build the hardware prototype with very simple materials and regular tools; a software development kit (SDK) to help with the development of new applications (e.g. augmented reality app); and, finally, a second SDK (ControlWear) to interact with mobile applications through a Smartwatch. Design/methodology/approach: User experiments were conducted, in which participants were asked to create, by themselves, the CARTON's hardware part and perform usability tests with their own creation. A second round of experimentation was conducted to evaluate three different interaction modalities. Findings: Qualitative user feedback and quantitative results prove that CARTON is functional and feasible to anyone, without specific skills. The results also showed that ControlWear had the most positive results, compared with the other interaction modalities, and that user interaction preference would vary depending on the task. Originality/value: The authors describe a novel way to create a smart eyewear available for a wide audience around the world. By providing everything open-source and open-hardware, they intend to solve the reachability of technologies related to smart eyewear and aim to accelerate research around it.